ADALIMUMAB FOR ULCERATIVE COLITIS: RESULTS OF A BRAZILIAN MULTICENTER OBSERVATIONAL STUDY - ZACHARIAS,Patrícia (2017)
ABSTRACT BACKGROUND: Adalimumab is a monoclonal antibody, tumor necrosis factor-alpha (TNFα) inhibitor that has efficacy for inducing and maintaining remission in moderate-to-severe ulcerative colitis. Real world studies with adalimumab in Latin American ulcerative colitis patients are scarce. OBJECTIVE: To assess the clinical remission rates in induction and maintenance with adalimumab therapy in ulcerative colitis. METHODS: Observational, multicenter and retrospective study on a case series of patients with moderate-to-severe ulcerative colitis under adalimumab therapy. The variables analyzed were: demographic data, previous infliximab status, concomitant drugs, the Montreal Classification, disease activity (Mayo score) at weeks 0, 8, 26 and 52, or until the last follow-up. Clinical remission was defined as a partial Mayo score ≤2 and Last observation carried forward (LOCF) and Non responder imputation (NRI) analysis were used. RESULTS: Thirty-six patients were included in the study. With LOCF analysis, remission rates at weeks 8, 26 e 52 were of 41.7%, 47.2% and 47.2%, respectively. With NRI analysis, remission rates at weeks 8, 26 and 52 were of 41.7%, 41.7% and 27.8%, respectively. CONCLUSION: Adalimumab was effective in the treatment of moderate-to-severe ulcerative colitis. Clinical remission was observed in approximately 40% of the patients at weeks 8 and 26, and in almost a quarter of the patients after 1 year of follow up.